Android mobile gripping robot - Tan, Kit Oon (2015)
Mobile gripping robot is one of the well known robot platform for development in the field of robotic. It is the best platform of robot before further develops into advance autonomous robot with picking object features. The main features of the mobile robot is able to be control wirelessly form a distance. This can be achieved by Bluetooth communication with an Android device. As the technology of Android operating system has been developing rapidly, it has been in of the most used platform in smartphones and it has been implements to control all kinds of peripheral devices like servos, motors and others. MIT App Inventor is one of the software available in the market which can be used for developing Android app. The main objective of this project is to develop an Android app using the MIT App Inventor software to control a mobile gripping robot. Additionally, this project is also to implement the feautres of an Accelerometer in an Android device to control the movement of the mobile gripping robot. The implementation of MIT App Inventor software ‘s block programming simplify the development of an Android app which can be used in the field of robotic to control a robot. Other than that, with MIT App inventor software the Accelerometer of an Android device can be used for control purpose too. The implementation of the Android device for controlling a mobile robot will save a lot of cost and time of the researchers of robotic field in building a controller for a premilinary stage robot. As the implementation of the Android device as controller of a mobile robot can be achieved by developing app using MIT App Inventor Software.